Model Pembelajaran Inkuiri Terbimbing Berbantuan Google Workspace for Education untuk Meningkatkan Hasil Belajar IPA - Ekayogi, I Wayan (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to improve learning outcomes of science content on the theme of always saving energy by applying a guided inquiry learning model assisted by google workspace for education for 4th grade students of SD Negeri 5 Sebatu, Tegallalang District, Gianyar Regency, the academic year 2021/2022. This type of research is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of stages of planning, action, observation/evaluation, and reflection. The implementation of the action in each cycle is three meetings. Data were analyzed by descriptive statistical analysis method and quantitative descriptive analysis method. The results showed that there was an increase in learning outcomes for science content on the theme of always saving energy. Based on the results of data analysis, the average percentage of student learning outcomes in science content in the first cycle was 67.78% (medium category), increasing to 83.15% (high category) in the second cycle.